T-helper 17 cytokines (interleukins 17, 21, 22, and 6, and tumor necrosis factor-α) in patients with alopecia areata: association with clinical type and severity - Atwa, Mona A.; Youssef, Nahed; Bayoumy, Nervana M. (International journal of dermatology, 2016)
Background Alopecia areata (AA) is an organ‐specific autoimmune disease characterized by T‐cell infiltrates and cytokine production. T‐helper 17 (Th17) cells are crucially involved in the pathogenesis of autoimmune diseases. Objectives Our aim was to assess the association of Th17 with AA. We examined interleukin (IL)‐17, IL‐21, IL‐22, IL‐6, and tumor necrosis factor‐alpha (TNF‐α) levels in the serum of patients with AA and studied their association with clinical type and severity of AA. Subjects and methods The serum concentrations of IL‐17, IL‐21, IL‐22, IL‐6, and TNF‐α were measured in 47 patients with AA and 40 healthy controls. The clinical type of AA was determined, and the severity of hair loss was assessed in accordance with the Alopecia Areata Investigational Assessment Guideline criteria. Results The serum concentrations of IL‐17, IL‐21, IL‐22, IL‐6, and TNF‐α were significantly higher in patients with AA as compared with healthy controls (mean: IL‐17 33.23 ± 11.58 vs. 4.62 ± 1.88 pg/ml; P = 0.000, IL‐21 62.10 ± 6.11 vs. 48.38 ± 3.31 pg/ml; P = 0.000, IL‐22 19.27 ± 3.36 vs. 7.09 ± 1.62 pg/ml; P = 0.000, IL‐6 17.18 ± 3.08 vs. 4.59 ± 1.66 pg/ml; P = 0.000, TNF‐α 19.94 ± 3.59 vs. 9.95 ± 2.42 pg/ml; P = 0.000, respectively). There were significant positive correlations between serum IL‐17, TNF‐α, and disease severity. There was also significant positive correlation between serum IL‐22 and duration of AA. Conclusion Our results showed high serum levels of Th17 cytokines among patients with AA that may suggest a functional role of these cytokines in the pathogenesis of this important skin disease. It could also provide the rationale for new treatment strategies in AA.